Lost highway das Ende der Straße ist erst der Anfang. - Badalamenti, Angelo 1937-2022 (Universum Film, 2002)
A successful jazz musician whose marriage is on the rocks, a man in black who threatens to expose him, a young mechanic with links to a mobster, and the mobster's moll are all riders on the lost highway, trapped in their worlds of desire, destiny and unknown destination.
Original: Thriller Frankreich, USA 1997
Bildformat: 2,35:1 Widescreen (16:9 codiert)
Special features: Interviews mit Cast & Crew, Trailer "Lost Highway", Trailer "The streight story"
Keywords: Feature films; Film; DVD-Video